Factores motivacionales en adolescentes que se realizaron cirugías estéticas antes de los 18 años, en la cuidad de Cartago Valle (2020)
The proposed research carried out a content description of the motivational factors that led a group of adolescent women to undergo cosmetic surgery before the age of 18, through an interview with a qualitative method and hermeneutical historical approach to four women with cosmetic surgeries, obtaining as results: extrinsic and intrinsic motivational factors according to the experience lived by the participants, the psychological needs of aesthetics and self-realization fed by beauty ideals motivate the performance of cosmetic surgeries.